1996
DOI: 10.1177/0361198196154100107
|View full text |Cite
|
Sign up to set email alerts
|

Proof Load Testing of Highway Bridges

Abstract: It is estimated that there are more than half a million highway bridges in the United States. Many of these bridges have deteriorated considerably because of age and inadequate maintenance and inspections, whereas the average daily truck traffic and truck loads have increased. Careful evaluation is required to make rational economic and safety decisions concerning the rehabilitation of each bridge. Proof load testing is an efficient tool that can be used to evaluate the performance of existing bridges. The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Proof loading 14,15 can be carried out on existing bridges. If a certain load can be carried, sufficient capacity is proven.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proof loading 14,15 can be carried out on existing bridges. If a certain load can be carried, sufficient capacity is proven.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reliability of bridge management systems depend on the successful integration of nondestructive testing and evaluation methods [29][30][31][32]. It has been observed from a bridge's response to the same load input over several months that the natural vibration frequency and flexibility coefficients may change as much as 10-15%, while local strain and global deflection responses may vary in the order of 5% [7].…”
Section: Nondestructive Testingmentioning
confidence: 99%
“…Most studies focused on impervious LWD jams; these studies potentially overestimated the effects of LWD on scour, since Parola et al. (2000) showed that porosity can have a great importance on the drag force applied to LWD at bridge piers. Pagliara and Carnacina (2010) tested scour at single bridge piers with LWD using two values of porosity (namely 0 and 0.6) and found that temporal evolution was similar across experimental tests.…”
Section: Introductionmentioning
confidence: 99%